Men’s Excessive Concern about Penile Size - Mikhael San Putra Wijanarko; Cathelin Stella; Grevy Yanika (Universitas Airlangga, 2022)
The dissatisfaction of men due to their penile size is found in a number of studies. Concerns can be focused on the penile length or width or even both, whether erect or flaccid. Men who are worried about the penile size also want to increase the size of the penis. Concerns about men’s penile size are also increasing because they think normal penile size is what is shown in pornography. These worries can affect self-esteem, sexual function, and satisfaction, to physical and mental health. Small penis anxiety is an anxiety that arises when a man observes his flaccid penile size and feels concerned that his penile size is less than the normal size. In addition, this concern persists even though it has been refuted by clinical examination. Penile dysmorphic disorder is excessive self-concern, distress, and a preoccupation with trivial or even non-existent deficiencies in penile size and shape that can lead to impaired function. Until now, there have not been effective guidelines for managing patients with complaints of penile size. Some of the treatments that can be conducted are psychosexual counseling, cognitive behavioral therapy, the use of selective serotonin reuptake inhibitors, penile traction devices, and invasive procedures. Various modalities of therapy have been tried to overcome excessive concern about penile size. Yet, so far, no good results have been obtained. Thus, clear and effective guidelines are needed to make treatment can be carried out properly.